2002
DOI: 10.1038/sj.bjp.0704618
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of LPS‐induced chemokine production in human lung endothelial cells by lipid conjugates anchored to the membrane

Abstract: 1 In acute respiratory distress syndrome (ARDS) induced by endotoxins, a high production of in¯ammatory mediators by microvascular lung endothelial cells (LMVEC) can be observed. Activation of cells by endotoxins may result in elevated secretion of phospholipase A 2 (sPLA 2 ) which is thought to contribute to tissue damage. The present study was undertaken to investigate the role of sPLA 2 in chemokine production in human lung microvascular endothelial cells (LMVEC) stimulated with the endotoxins lipopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…In addition to lipid mediator production, PLA 2 activity is also linked to the production or action of other agents involved in skin inflammation, such as IL-I in murine DTH (19), IL-8 in stimulated dermal fibroblasts (20), iNOS in psoriasis (21) and contact dermatitis (22), the T-cell adhesion molecules (23) and TNFa in psoriasis (24). Concordant with this, the ExPLIs were found effective in suppression of these mediators and amelioration of related inflammatory conditions in a number of in-vitro and in-vivo systems, including the suppression of endotoxin-induced production of cytokines and adhesion molecules in human lung microvascular endothelial cells (13), as well as in rats with endotoxin-induced sepsis (12), rats and mice with experimental allergic encephalomyelitis (EAE) (25), and rats with ovalbumin-induced allergic bronchitis (14).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition to lipid mediator production, PLA 2 activity is also linked to the production or action of other agents involved in skin inflammation, such as IL-I in murine DTH (19), IL-8 in stimulated dermal fibroblasts (20), iNOS in psoriasis (21) and contact dermatitis (22), the T-cell adhesion molecules (23) and TNFa in psoriasis (24). Concordant with this, the ExPLIs were found effective in suppression of these mediators and amelioration of related inflammatory conditions in a number of in-vitro and in-vivo systems, including the suppression of endotoxin-induced production of cytokines and adhesion molecules in human lung microvascular endothelial cells (13), as well as in rats with endotoxin-induced sepsis (12), rats and mice with experimental allergic encephalomyelitis (EAE) (25), and rats with ovalbumin-induced allergic bronchitis (14).…”
Section: Discussionmentioning
confidence: 79%
“…Simultaneously, the lipid anchors the GAG to the membrane, thus elevating GAG levels on the cell surface. The ExPLIs have been previously found effective in suppressing diverse inflammatory and allergic processes in vitro and in vivo (12)(13)(14). In this paper we report the results from a double blind placebo-controlled pilot study in contact dermatitis patients using a I% topical preparation of an ExPLI.…”
mentioning
confidence: 98%
“…It appears therefore the ExPLIs exert a dual effect in protecting cells from proinflammatory agents. The lipid component, which is incorporated into the cell membrane, suppresses the activation of endogenous sPLA 2 , whereas the polymeric carrier mimics the cell surface GAG in protecting the membrane from the action of extracellular PLA 2 and other inflammatory mediators (Yedgar et al, 1995; Ginsburg et al, 1997; Balsinde et al, 2000; Beck et al, 2002; Yard et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study has shown that ExPLIs can block the INFγ‐induced expression of MHC class II and I and of mixed lymphocyte reaction‐induced T‐cell proliferation and cytokine secretion (Yard et al, 2002). Furthermore, we previously found that these membrane‐anchored lipid conjugates can effectively block endotoxin‐induced production of chemokines and adhesion molecules, as well as the activation of NF‐κB (Beck et al, 2002). Due to their structure, the lipid conjugates fulfill a multiple function in cell protection: the lipid moiety, which is incorporated into the cell membrane, suppresses the activity of endogenous sPLA 2 (Ginsburg et al, 1997; Balsinde et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…18,[27][28][29][30] Accordingly, the control of PLA 2 activities has been proposed (and attempted) for the treatment of numerous inflammatory conditions, including respiratory inflammatory/allergic diseases. [31][32][33][34][35][36][37] Despite the studies that link CRS pathophysiology to the production of AA-derived metabolites, the role of PLA 2 activities in CRS has not been studied, except for the study by Liu et al, 38 that reported the expression of PLA 2 of group II (IIA, IID, IIE) in nasal tissues of CRS with or without polyps, subsequent to stimulation with IL-1␤ or tumor necrosis factor ␣. However, this study did not test the effect of inhibiting PLA 2 expression and thus did not directly address the role of these PLA 2 types in the pathogenesis of CRS pathology.…”
mentioning
confidence: 99%